The effects of work/life balance towards employee satisfaction in Sarawak Energy Berhad - Siti Fattimah Zahra, Binti Khaidzir (Universiti Malaysia Sarawak (UNIMAS), 2013)
The study was conceptualized out of the burgeoning issues with regards to collective union/employee dissatisfaction over work/life imbalances faced nowadays, in Sarawak Energy Berhad. Given past documentations of negative consequences of work/life conflict towards satisfaction level among employees, the study was therefore initialized to investigate the perception of work/life balance and employees' level of satisfaction, as well as to determine the relationship between employee satisfaction and work/life balance given the interwoven connection between both criterions) Based upon the purported "inter-role conflict" concept, an extension of the "role theory" and the "spillover theory", the framework explains the anticipated relationship between both variables. A self-administered questionnaire to elicit the socio-demographic profile, perceptions of work/life balance and employee satisfaction levels were distributed to n=J00 samples, and data was analyzed using 50 returned questionnaires. The correlation analysis to test the hypothesis revealed that there is no significant relationship between employee satisfaction and work/life balance. The results contradict to the common notion as explored from previous researches, giving rise to the possible effects or presence of other mediators such as cultural tendencies, e.g. family-centered and respect for authority, as well as professionalism levels e.g. commitment and dedication to the job. The findings may pave way for further research in the mediating factors that may influence the relationship as well as beneficial for use and consideration of the management in areas of employees' personal development.